2015
DOI: 10.3390/w7084232
|View full text |Cite
|
Sign up to set email alerts
|

Daily Reservoir Runoff Forecasting Method Using Artificial Neural Network Based on Quantum-behaved Particle Swarm Optimization

Abstract: Accurate daily runoff forecasting is of great significance for the operation control of hydropower station and power grid. Conventional methods including rainfall-runoff models and statistical techniques usually rely on a number of assumptions, leading to some deviation from the exact results. Artificial neural network (ANN) has the advantages of high fault-tolerance, strong nonlinear mapping and learning ability, which provides an effective method for the daily runoff forecasting. However, its training has ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…Therefore, more complex nonlinear models such as artificial neural networks (ANNs) have been applied for better estimation in recovering streamflow [14][15][16]. Previous studies [9,17,18] have reported as well that the self-organizing map (SOM), an unsupervised ANN, showed satisfactory imputation results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more complex nonlinear models such as artificial neural networks (ANNs) have been applied for better estimation in recovering streamflow [14][15][16]. Previous studies [9,17,18] have reported as well that the self-organizing map (SOM), an unsupervised ANN, showed satisfactory imputation results.…”
Section: Introductionmentioning
confidence: 99%
“…First, to improve the model performance, the MLMs have been combined with statistical methods, including phase-space reconstruction [22,23], principal component analysis [24,25], fuzzy c-means clustering [7,22], k-means clustering [26,27], self-organizing map (SOM) [28,29] and bootstrap [30]. Second, the MLMs have been coupled with evolutionary optimization algorithms, including genetic algorithm (GA) [31,32], particle swarm optimization (PSO) [11,33], artificial bee colony [34], bat algorithm [35], and firefly algorithm [36]. The addressed algorithms were very helpful for efficient model learning and optimal parameter searching.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further prove the optimization performance of the proposed IPSO in training the FNN model, the basic PSO [26], quantum-behaved PSO (QPSO) [27], opinion leader-based QPSO (OLB-QPSO) [28], and Laplace PSO (LPSO) [29] were employed to optimize the parameters in the FNN model. The parameters were set according to the relevant literatures.…”
Section: Field Applicationmentioning
confidence: 99%